SHORT-FORM CONTENT, BRAIN ROT, AND BED ROT: A LITERATURE REVIEW OF THE IMPACT ON UNIVERSITY STUDENTS - Aysi, Alya Muhkbita Tasya Nur; Firdaus, Amanda Rahma; Pangestu, Surya Marcello; Utomo, Hanggara Budi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study examines the cognitive and behavioral impacts of excessive short-form content consumption among university students, focusing on the phenomena of "brain rot" (cognitive decline) and "bed rot" (sedentary digital overuse). Method: This study employs an exploratory literature review method to investigate emerging phenomena related to short-form content consumption and its impacts—such as brain rot, bed rotting, and procrastination—among university students. Unlike systematic literature reviews, which typically focus on more specific research questions, the exploratory approach allows for a broader and more flexible investigation of new concepts in the relatively nascent field of digital media research. Results: Findings indicate that heavy social media use: (1) reduces prefrontal cortex density, impairing attention and memory; (2) decreases academic performance (30% lower information retention, GPA declines); (3) increases procrastination and mental health issues (anxiety, depression); and (4) creates addictive dopamine feedback loops. The "bed rot" phenomenon further exacerbates these effects through physical inactivity and sleep disruption. Novelty: This review is among the first to synthesize neurological, behavioral, and academic evidence into a unified framework, proposing actionable interventions at individual and institutional levels. Our findings highlight the urgent need for digital wellness strategies in higher education.